Identifying and understanding the patterns and processes of forest cover change in Albania and Kosovo - Kuenda Laze (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Forests are important resources for local livelihoods and the economy. Forest cover can be significantly affected by changes in institutional and political framework conditions such as induced by the collapse of socialism in Eastern Europe and the war in Kosovo. This study analyzed the determinants of changes in forest cover for two periods between 1988 and 2007 for Albania and Kosovo. The method used in this thesis included Geographically Weighted Regression (GWR) that served to identify the local pattern and processes of forest cover change. Pressures on forest from subsistence extraction of wood decreased in the second period when deforestation was observed in larger distance from roads and populated areas. The determinant of distance to nearest human settlement showed high local variations in their relationships with forest cover change. A strong negative influence was particularly evident in the northern and northeastern regions in Albania and the northern and southern in Kosovo in the second period. This research contributed important country-evidence to the literature on the patterns and processes of the post-socialist forest cover change. – – Wälder sind eine wichtige Ressource für die Lebensbedingungen und die Wirtschaft in einer Region. Das Ausmaß der Waldbedeckung kann in hohem Maße von institutionellen und politischen Rahmenbedingungen beeinflusst werden, wie etwa dem Ende des Sozialismus in Osteuropa oder dem Kosovokrieg. In dieser Studie werden Determinanten für die Veränderung der Waldbedeckung in Albanien und dem Kosovo für zwei Zeiträume zwischen 1988 und 2007 untersucht. Zu den in dieser Arbeit verwendeten Methoden zählt die Geographically Weighted Regression (GWR), die zur Feststellung regionaler Muster und Prozesse in der Veränderung der Waldbedeckung genutzt wurde. Die Belastung auf den Wald durch existenzsichernde Holzgewinnung war im zweiten Untersuchungszeitraum, für den eine Entwaldung in größerer Entfernung von Straßen und Siedlungen zu beobachten war, geringer. Die Determinante Entfernung zu menschlicher Besiedelung zeigte im Zusammenhang mit der Veränderung der Waldbedeckung starke lokale Unterschiede auf. Besonders negativen Einfluss dieser Determinante auf die Waldbedeckung ließ sich vor allem in den nördlichen und nordöstlichen Gebieten Albaniens und den nördlichen und südlichen Regionen des Kosovo im zweiten Untersuchungszeitraum feststellen. Diese Studie leistet somit einen wichtigen Beitrag zur Literatur, insbesondere im Hinblick auf Ergebnisse zu Mustern und Prozessen der postsozialistischen Veränderungen der Waldbedeckung in den betrachteten Ländern.
urn:nbn:de:gbv:3:2-31678
Keywords: 330